Optimization of the Level of Mushroom in Analogue Meat Nuggets - Kumar, Pavan; Sharma, B.D.; Kumar, R. R. (Journal of Meat Science, 2011)
Meat analogue is mock meat that is made from non-animal protein and its appearance and smell are very much like real meat. Analogue meat nuggets were prepared as per basic formulation under standardized processing conditions with three different levels of mushroom viz. 18%, 22.5% and 27% replacing textured soy protein. Among the physico-chemical parameters pH and protein percent decreased significantly (P
Keywords: Level of Mushroom; Analogue; Meat Nuggets; non-animal protein